Juridical Review of Motorcycle Drivers with the Level of Safety at SMP Negeri 1 Padaherang - Dimas Adittia Nugraha (Proceedings Series on Social Sciences & Humanities, 2023)
The development of the times has made the younger generation have a lot of expertise in all fields,but on the other hand many young people are doing social deviations today. One of them was riding a motorbike by a minor. The facilities provided by parents aim to make it easier to study at school. This study aims to determine the level of vehicle use by minors and the level of safety, the factors that influence the use of vehicles by minors and to analyze in order to find out more about the use of motorized vehicles by minors in the Pangandaran Regency area. especially at SMP NEGERI 1 PADAHERANG. The results of the study showed an increase in the number of underage drivers, especially at SMP NEGERI 1 PADAHERANG School students in the Pangandaran Regency area. Factors in the use of motorized vehicles by minors are internal factors and external factors. The policy strategy for preventing the motor level of vehicle use by students in Pangandaran Regency is by means of preventive and repressive efforts.